Zasada zabudowy planowej jako środek służący realizacji celów państwa autorytarnego na podstawie przepisów ustawy z dnia 12 lipca 1984 roku o planowaniu przestrzennym - Błażewski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The principle of planned spatial development was common in the socialist period. It was both a tool to protect the economic interests of the state, and a legal instrument of the authoritarian state at the time. Its scope and application was general, and as such it resulted a disproportionate restriction of the individual’s ownership rights, far exceeding the needs of public interest. The institutions that applied it, i.e. the state administration authorities, had no democratic legitimacy. The principle of planned spatial development has not connotations with any type of political system, by its very nature. It might as well function as a legal measure in democratic states. In Poland it is currently applied in specific cases. The Swiss legal order assumes general application of this principle by public administration authorities, who have democratic legitimacy.
Keywords: zabudowa; planowanie przestrzenne; plan gospodarczy; autorytaryzm; wolność zabudowy; zabudowa planowa